Financial Distress, Corporate Restructuring and Firm Survival An Empirical Analysis of German Panel Data - Jostarndt, Philipp; SpringerLink (Online service) (Wiesbaden : Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2007)
The economic ramifications of corporate financial distress and bankruptcy have recently gained much attention in academic as well as public policy debates. But empirical evidence on how firms encounter and respond to distress has remained sparse and inconclusive. Philipp Jostarndt analyzes the anatomy of financial distress for a large sample of German corporations. He studies distress-induced changes in ownership and control, success factors in distressed equity infusions, and firms’ choice between in- and out-of-court debt restructurings. Moreover, he conducts a survival analysis to examine the determinants of survival, acquisition, and bankruptcy as alternative paths to exit financial distress. He includes both the firm perspective as well as the market valuations of the undertaken restructurings and, where applicable, relates the findings to the microstructure of Germany’s revised bankruptcy legislation.
Data selection and sample descriptives -- Financial distress, corporate control, and management turnover: A German panel analysis -- Of bail-outs and bankruptcies: An empirical study of distressed debt restructurings in Germany -- Claimholder conflicts in distressed equity offerings: Evidence from German restructurings -- A study of firm exit and survival in financial distress.
Keywords: Leadership; Finance; Business Strategy/Leadership.; Finance, general